The carnivorous plant Genlisea harnesses active particle dynamics to prey on microfauna - José Martín-Roca; C. Miguel Barriuso G.; Raúl Martínez Fernández; Camila Betterelli Giuliano; Rongjing Zhang; Chantal Valeriani; Laurence G. Wilson (Proceedings of the National Academy of Sciences, 2025)
Carnivory in plants is an unusual trait that has arisen multiple times, independently, throughout evolutionary history. Plants in the genus Genlisea are carnivorous and feed on microorganisms that live in soil using modified subterranean leaf structures (rhizophylls). A surprisingly broad array of microfauna has been observed in the plants’ digestive chambers, including ciliates, amoebae, and soil mites. Here, we show, through experiments and simulations, that Genlisea exploit active matter physics to “rectify” bacterial swimming and establish a local flux of bacteria through the structured environment of the rhizophyll toward the plant’s digestion vesicle. In contrast, macromolecular digestion products are free to diffuse away from the digestion vesicle and establish a concentration gradient of carbon sources to draw larger microorganisms further inside the plant. Our experiments and simulations show that this mechanism is likely to be a localized one and that no large-scale efflux of digested matter is present.